Unconventionally Made-Cellular Glass Aggregate - Lucian Paunescu; Sorin Mircea Axinte; Felicia Cosmulescu (Newinera Publisher, 2021)
Improving the original manufacturing process in microwave field of a cellular glass aggregate using a recipe containing colored consumed drinking bottle, calcium carbonate (CaCO3) as an expanding agent, sodium borate (borax) as a fluxing agent and sodium silicate (Na2SiO3) as a binder is shown in the work. The main adopted technological measures were the advanced mechanical processing of residual glass at a grain dimension below 100 μm and especially the use of a high electromagnetic wave susceptible ceramic tube with a wall thickness reduced from 3.5 to 2.5 mm for the protection of the pressed glass-based mixture against the aggressive effect of microwave field and, in the same time, to achieve a preponderantly direct heating with electromagnetic waves. Of the tested variants, a recipe with 1.6 % calcium carbonate, 6 % borax, 8 % sodium silicate and the rest residual glass was determined to be optimal. The cellular glass aggregate had the bulk density of 0.22 g/cm3, heat conductivity of 0.079 W/m·K and compression strength of 5.9 MPa. The specific consumption of energy was very low (0.71 kWh/kg) below the range of reported values of the industrial processes consumption (between 0.74-1.15 kWh/kg).